APLIKASI E-ARSIP PADA SATUAN KERJA PERENCANAAN DAN PENGENDALIAN DINAS PEKERJAAN UMUM PROVINSI JAMBI: APPLICATION, ARCHIVING, EMPLOYE - Sany, Ezrifal (FORTECH (Journal of Information Technology), 2018)
The number limited of employees in the processing of document data and correspondence, Satuan Kerja Randal want to build an application that can assist in the process of archiving documents. By using application documents, the documents can be stored in digital form that can save storage, in addition to electronic data can facilitate users, especially in searching documents and letters that have been past. The process of structuring documents can be done well without fear of loss of documents. With the application is expected to improve employee performance for the better, because the administrative data has been computerized so that the work process more effective and efficient.